Arduino: a simple and affordable solution for electrifying acoustic drums - Costa, Vinícius Souza; Oliveira, Haniel Taynã Pedreira de; Santos Júnior, José Wilson Passos dos; Pereira, Luan Diego de Lima (Brazilian Journal of Production Engineering, 2024)
This study focuses on the electrification of acoustic drums, adopting Arduino as a cost-effective and efficient solution to enhance the sonic capabilities of these instruments. The electrification process involves the strategic incorporation of piezoelectric sensors into various drum components, converting mechanical vibrations from drumstick contact into electrical signals. These signals, processed by Arduino, are then directed to dedicated Software, enabling precise emulation of the sounds associated with each drum component. The choice of Arduino as an electronic prototyping platform is supported by its versatility, financial accessibility, and user-friendly learning curve. The implementation of this approach brings substantial improvements, including a notable optimization in the drum's sound quality, flexibility for custom sound adjustments, providing musicians with refined control over their performance, and reducing ambient noise, expanding possibilities for performances in diverse contexts. This study not only highlights technological advancements in the musical field but also underscores the importance of innovative and economically accessible solutions, contributing to the democratization of technology access across various application domains.
Keywords: Electrification; Arduino; Sound quality; Technological innovation